Analisis Implementasi SAK Nomor 101 pada Laporan Keuangan di KSPPS BMT UGT Nusantara Capem Kepanjen - Manan, Yuliyanti M.; Fatimah, Devi Sofiyatul (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2024)
This study aims to determine the understanding of the management of KSPPS BMT UGT Nusantara Capem Kepanjen Malang about SAK number 101 in the presentation of Islamic financial statements and to determine the application of SAK No. 101 in the presentation of Islamic Financial Statements at KSPPS BMT UGT Nusantara Capem Kepanjen Malang. The type of research used is qualitative research with descriptive analysis. Data collection methods through observation, interviews, and documentation. The results showed that the board only understood the broad meaning of financial statements but did not understand the components contained in each item of financial statements by Sharia principles and SAK No. 101. As for applying SAK number 101 in the presentation of Islamic financial statements at KSPPS BMT UGT Nusantara Capem Kepanjen Malang, it has implemented SAK No. 101 in the presentation of its financial statements.